The Development of Pet Blood Donor Mobile Application for Empire Animal Medical Centre - Kheo Tay, E Thing; Darman, Rozanawati (Applied Information Technology And Computer Science, 2024)
Since pet blood banks are not yet well established, finding a matching pet blood donor is very difficult. The Pet Blood Donor mobile application is designed to facilitate the process of finding matching cat and dog blood donors for pet blood transfusions. This application has two types of users: veterinary staff as admins and pet owners as users. The application allows users to schedule an appointment to check pet blood donation eligibility and view pet blood donation history while admins manage these records through a website. Object-Oriented Analysis and Design (OOAD) is the methodology used to develop this application. Android Studio is used to develop the application, and Visual Studio Code is used to develop the web-based admin side. Firebase is used to store the database. In summary, the application is expected to increase pet blood donation awareness, increase potential pet blood donors, and ensure timely blood supply for pets.